Functional Properties, Antioxidant Activity, and Organoleptic Quality of Novel Biscuit Produced by Moroccan Cladode Flour “Opuntia ficus-indica” - Bouchra Nabil; Rachida Ouaabou; Mourad Ouhammou; Lamia Essaadouni; Mostafa Mahrouz (Journal of Food Quality)
This study aimed to develop a novel biscuit by supplementing cladode flour (CF) into whole-wheat flour (WWF) at different proportions 0, 25, 50, 75, and 100%. Proximate analysis revealed that CF had a high amount of ash (11.9%) and dietary fiber (41.04%). Major minerals determined by ICP-MS were calcium (4.47 g/100 g); potassium (1.25 g/100 g); magnesium (1.46 g/100 g); and trace elements such as zinc (1.77 mg/100 g), copper (0.95 mg/100 g), and selenium (148.5 μg/100 g). The analysis of total phenolics, total flavonoids, and antioxidant activity showed high values (649.88 mg gallic acid equivalents (GAE)/100 g; 399.16 mg catechin equivalent (CE)/100 g; and 72.37%, respectively). HPLC was used to identify four phenolic acids (gallic, ferulic, syringic, and caffeic acids) and only one flavonoid (rutin) in cladode flour. Biscuit hardness, L∗, and a∗ color values decreased corresponding to the incorporation level of CF. Sensory evaluation showed that the substitution level (up to 25%) is ideal to prepare an acceptable bio-biscuit. Cladode flour could be very useful for the food industry as a source of bioactive compounds with technological potential and nutritional and antioxidant properties.